2012
DOI: 10.1016/j.clim.2012.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The developing human preterm neonatal immune system: A case for more research in this area

Abstract: Neonates, particularly those born prematurely, are among the most vulnerable age group for morbidity and mortality due to infections. Immaturity of the innate immune system and a high need for invasive medical procedures in the context of a preterm birth make these infants highly susceptible to common neonatal pathogens. Preterm infants who survive may also suffer permanent disabilities due to organ damage resulting from either the infection itself or from the inflammatory response generated under an oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
137
0
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 166 publications
(151 citation statements)
references
References 86 publications
3
137
0
11
Order By: Relevance
“…The immune system of a full-term infant is thought to be well-adapted to its developmental period [19,31]. Most recently, studies have demonstrated other unique functional features of the newborn immune system, potentially allowing age-specific interactions between innate and adaptive immune cells during the course of an infection.…”
Section: Box 2 Relative Importance Of the Innate And Adaptive Immune mentioning
confidence: 99%
“…The immune system of a full-term infant is thought to be well-adapted to its developmental period [19,31]. Most recently, studies have demonstrated other unique functional features of the newborn immune system, potentially allowing age-specific interactions between innate and adaptive immune cells during the course of an infection.…”
Section: Box 2 Relative Importance Of the Innate And Adaptive Immune mentioning
confidence: 99%
“…[45][46][47][48][49] Preterm infants also have a limited ability to counteract inflammatory and oxidative stress during the neonatal period. 50 Sustained oxidative stress and inflammation are key factors contributing to the development of BPD as well as other neonatal complications. Dietary LCPUFA, particularly DHA and eicosapentaenoic acid are important modulators of inflammation.…”
Section: Figurementioning
confidence: 99%
“…Neonates and in particular preterm infants are extremely vulnerable to states of inflammation [1]. They have an increased susceptibility to microbial infections with an enhanced morbidity and Correspondence: Mr. Thomas Winterberg e-mail: Winterberg.thomas@mh-hannover.de mortality [2].…”
Section: Introductionmentioning
confidence: 99%